Individual Performance Management: A Review of Current Practices - Ian O’ Boyle (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
This paper provides a review of current practice in relation to individual performance management systems and process within the traditional business environment. There is a consensus that the role of the individual is central to the overall performance of any organization and how individual performances are managed and evaluated can have significant impacts on overall organizational success. Many organizations employ the traditional performance appraisal in order to monitor and assess individual employee performances. However, new approaches, such as 360-degree feedback have also become commonplace within the business environment. An analysis of each approach including benefits and challenges associated with each process is presented within this paper.